Buying and selling Civil War memory in gilded age America - Marten, James Alan (Uncivil wars., 2021)
"Buying and Selling the Civil War is a collection of original essays about the marketing and selling of Civil War memory during the postwar economic boom known as the "Gilded Age." The editors, Marten and Janney, both renowned scholars for their studies of the Civil War, provide a new framework for examining the intersections of material culture, consumerism, and contested memory. Each essay offers a case study of a product, experience, or idea related to how the Civil War is remembered and memorialized. Taken together, these essays trace the ways the buying and selling of the Civil War shaped Americans' thinking about the conflict. As one reviewer points out, this volume makes an "important contribution to scholarship on Civil War memory" and extends our understanding of subjects as varied as "print culture, visual culture, popular culture, finance, the history of education, the history of the book, and the history of capitalism in this period." The volume's contributors include Crompton B. Burton, Kevin R. Caprice, Shae Cox, Jonathan S. Jones, David K. Thompson, Amanda Brickell Bellows, Natalie Sweet, Jonathan W. White, Anna Gibson Holloway, Barbara A. Gannon, Edward John Harcourt, Margaret Fairgrieve Milanick, Paul Ringel, and John Neff"--